FACTORS AFFECTING THE NON PERFORMING LOAN - Sari, Pipit Buana (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2019)
Credit is accounts receivable which represents the cash that delayed its acceptance, so the presence of bad credit is a factor that can make the weak condition of an institutional financial and non-financial. This study aims to determine the influence of factors internal and external to the Non-Performing Loan on PT. Bank Rakyat Indonesia Tbk. This study uses the method of descriptive qualitative. The study population is the debtor in the PT. Bank Rakyat Indonesia Tbk Branch Binjai as many as 172 people and take 6 people, customers, as the sample of the study. Researchers use interview techniques to gather research data. Then based on the results of the research can be concluded there is the influence of internal factors which causes bad credit in some the absence of a clear separation between the personal property and company. If viewed from the side of the externalities then factor the causes of the credit jammed the misuse of credit made by the customer to the business that they manage. So it can be said that there is an influence between the internal and external factors on bad credit on PT. Bank Rakyat Indonesia Tbk Cabang Binjai. If implementation and management of internal factors and external customers are less good then it will cause a reduction in revenue on the business customer so resulting in bad credit at PT. Bank Rakyat Indonesia, Tbk Branch of Binjai.